The Impact of Employee Performance and Service Quality on Public Satisfaction at BUMDES Ujan Mas Baru - Emiyati; Novita Sari; Yenni Suryono; Selvi Permata Sari (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2026)
The objective of this research is to understand and analyze the combined effects of employee performance and service quality on community satisfaction in the village of Ujan Mas Baru. The methodology employed is quantitative, specifically utilizing purposive sampling. The sampling technique will refer to Slovin's formula, with a sample size of 100 respondents. The findings of this study indicate that the correlation coefficient (r) is 0.691, which signifies a correlation between the employee performance variable and service quality with community satisfaction of 0.691. The calculated value of rhitung > rtabel is 0.691 > 0.196. This indicates a strong relationship, as the value of r falls within the range of 0.61 - 0.80. The calculated value of thitung > ttabel is 2.273 > 1.984, and the probability (significance) is < 0.05 (α), specifically 0.025 < 0.05, leading to the rejection of H0. This implies that the employee performance variable has a significant partial (individual) effect on community satisfaction. Furthermore, the calculated value of thitung > ttabel is 6.624 > 1.984, and the probability (significance) is <0.05 (α), specifically 0.000 < 0.05, resulting in the rejection of H0, indicating that the service quality variable also has a significant partial (individual) effect on community satisfaction. The simultaneous testing yields a calculated value of Fhitung > Ftabel of 86.257 > 3.09, with a p- value of 0.000. The results of the testing indicate a p-value that is less than the level of significance (α = 5%). This implies that there is a significant simultaneous effect of Employee Performance and Service Quality on Community Satisfaction, with a coefficient of determination value obtained at 0.633. The adjusted Rsquare value, which is the adjusted R2, stands at 0.633 or 63.3%, signifying that the variables of Employee Performance and Service Quality account for 63.3% of the influence on Community Satisfaction. The remaining 36.7% is attributed to other factors.